Biomechanical effects of root/cortical bone relation on tooth movement during premolar-extraction space closure with clear aligners: a finite element study - Dong, Yihan; Wang, Ya; Yang, Zun; Gong, Weiyi; Guo, Man; Wu, You; Hu, Yun; Zheng, Leilei (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study aimed to evaluate the biomechanical effects of varying sagittal root position (SRP), root length (RL), and cortical bone thickness (CBT) on tooth movement and stress distribution during clear aligner therapy (CAT) in extraction cases, using finite element analysis.MethodsThree-dimensional finite element models, including the maxillary alveolar bone, periodontal ligament (PDL), dentition, and clear aligner, were constructed. Groups with varying SRP (labial, middle, and palatal), RL (long, normal, short) and CBT (1 mm, 2 mm) were established. Tooth movement and stress distribution were analyzed for each group after 0.2 mm anterior tooth retraction.ResultsWithout attachments or additional forces, clear aligners (CAs) resulted in lingual tipping, extrusion, and distal movement of the central incisor in extraction cases. A labially positioned root amplified lingual tipping and torque loss, whereas a palatally positioned root preserved torque but increased posterior anchorage loss; moreover, shorter roots accentuated tipping and generated peak PDL stresses at the cervical and apical regions, while thinner cortical bone resulted in higher stress.ConclusionSRP and RL significantly affect tooth movement and stress distribution during anterior tooth retraction with CAs in extraction cases, while CBT has minimal impact in tooth movement. The optimal pre-retraction state involves a crown-to-root ratio not exceeding 1.1, with the root positioned upright in the cancellous bone, preventing contact with the labial or palatal cortical bone.